Pyrimethamine inhibits cell growth by inducing cell senescence and boosting CD8+ T-cell mediated cytotoxicity in colorectal cancer - Haiyan Dong; Limei Hu; Weiqian Li; Mengchen Shi; Lingyuan He; Chen Wang; Yijia Hu; Huihui Wang; Chuangyu Wen; Huanliang Liu; Xiangling Yang (Molecular Biology Reports, 2022)
Background The emergence of nonresponse or resistance to traditional chemotherapeutic agents is one of the main challenges of colorectal cancer (CRC) therapies. Thus, novel therapeutic drugs that can improve the clinical outcomes of CRC patients are urgently needed. The purpose of this study was to investigate the effects and mechanisms of pyrimethamine in CRC. Methods and results In this study, we assessed the role of pyrimethamine on CRC cell growth by cell counting kit-8 and colony formation assays. Cell cycle distribution and cellular senescence were determined by flow cytometry and senescence-associated β-galactosidase staining respectively. RNA-seq analysis and western blotting were used to investigate the potential pathways of pyrimethamine in CRC development. Moreover, animal experiments were performed to evaluate the effect of pyrimethamine in vivo. Our results demonstrated that pyrimethamine could inhibit cell growth by inducing S phase arrest followed by cellular senescence in CRC cells, and the p38MAPK-p53 axis was probably involved in that effect. In addition, pyrimethamine could also boost CD8 + T-cell mediated cytotoxicity and exert antitumor activity in vivo. Conclusion These results indicated that pyrimethamine may be a promising candidate agent for CRC treatment.